The effect of diet quality and body mass index on depression in older adults: a growth curve analysis - Yun-Lin Wang; Yun-Han Wang; Dara Kiu Yi Leung; Gloria Hoi Yan Wong; Terry Yat Sang Lum (BMC Geriatrics)
Abstract Background Nutrition not only plays an important role in one’s physical health, but also mental health. The causal association between nutrition and mental health remains unclear. While a healthy dietary pattern may protect one against mental illness, it is also possible that poor mental health could lead to unhealthy eating habits or choices. Furthermore, emerging studies suggest that a higher body mass index (BMI) is associated with a lower risk of depressive symptoms in older adults, contrasting the effect observed in other populations. With an ageing population, this study aimed to investigate the long-term impact of a healthy dietary pattern, BMI, and other covariates on depressive symptoms in older adults. Methods We conducted a cohort study between 2014 and 2017, with each follow-up assessment being one year apart. A total of 2081 participants above 65 years old (M = 79.65, SD = 7.94) completed the baseline assessment in 2014, which included basic demographics, self-reported eating habits, depressive symptoms, and the measurement of height and weight. Distance to supermarkets and fast food was calculated based on participants’ residential addresses. Two growth models were performed to assess the trajectory of change in depressive symptoms over time. Results Older adults experienced a significant decrease in depressive symptoms over time (intercept = 2.68, p < .001; slope = -0.25, p < .001). At baseline, a higher diet quality (B = -0.95, p < .001), higher BMI (B = -0.09, p < .001), younger age (B = 0.40, p = .001), being a male (B = 0.76, p < .001), and having fewer chronic diseases (B = 0.39, p < .001) were associated with lower levels of depressive symptoms. Over time, a higher diet quality (B = 0.14, p = .05), higher BMI (B = 0.02, p = .04), and fewer chronic diseases (B = -0.08, p < .001) predicted lower levels of depressive symptoms over time. Conclusions A higher diet quality and higher BMI may serve as protective factors for depressive symptoms in older adults. Potential implications are being discussed.